The petrogenesis of the older (> 3.0 Ga) potassic granitoids of eastern Mpumalanga (South Africa) and Swaziland : an investigation of crustal formation processes in the early Earth - Sanchez-Garrido, Cynthia J. M. G. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.